Women Representation in The Devil Wears Prada Movie - Natih, Putu Gayatridevi Ganti Karuni (Universitas Padjadjaran, 2024)
Although women have equal opportunities in the modern era, there are still certain expectations that push them to choose either a successful career or a stable personal life, which can make establishing and maintaining a career challenging. From a gender perspective, this study will analyze how The Devil Wears Prada (2006) portrays the struggle that women have to face while maintaining and setting up their careers. This study aims to analyze how women are represented in The Devil Wears Prada (2006), particularly focusing on the portrayal of career-oriented women and the conflicts they face in balancing their professional ambitions with personal relationships. The findings reveal the conflict between career success and personal life portrayed in the movie. Miranda’s career goals come at the cost of her personal relationships, while Andy is faced with similar tensions as her career path breaks away from her personal life.